Key stakeholders, platforms, and networks in Bangladesh’s food systems transformation process, 2022–2024 - Abedin, Jainal; Herens, Marion; Brouwer, Inge D. (International Food Policy Research Institute, 2024)
In 2022, the CGIAR Research Initiative on Sustainable Healthy Diets through Food Systems Transformation (SHiFT) conducted a stakeholder identification and analysis activity to develop its strategy for stakeholder engagement. As part of SHiFT’s Work Package 5, Catalyzing Food Systems Transformation, this analysis was used to prepare a stakeholder engagement strategy for Bangladesh, Ethiopia, and Viet Nam, SHiFT’s three countries of work. The stakeholder identification and mapping, as well as a report on the country’s food system transformation process and issues, constitute a database that enables rapid selection of potential stakeholders for engagement, capacity sharing, and collaboration, among other purposes. The stakeholder identification process is repeated, typically on a quarterly basis, to update the database. This summary report is based on information first collected in 2022 and updated as of December 2024. Building understanding, engagement, and capacity with diverse food system stakeholders will help to foster collaboration and coordination across varied perspectives, and to drive transformative actions across the food system for positive outcomes on the environment, food security and nutrition, and livelihoods and inclusion. SHiFT’s approach is to engage with and provide technical support to relevant stakeholders, networks, and platforms whose objectives are aligned with the Initiative’s goals. This approach aims to contribute to local and national food systems transformation for sustainable healthy diets, rather than facilitating the formation of new networks or platforms that would require more time to build engagement and capacity, and might not be sustainable. The Initiative’s efforts are also meant to avoid overlapping with those of the country’s government and other development partners. Instead, SHiFT aims to create synergies through coordinated actions to achieve national food systems transformation and sustainable healthy diets, as well as broader national goals on food systems.